Histological structure and histochemical composition of the digestive tract of salema porgy, Sarpa salpa (Linnaeus, 1758) (Teleostei: Sparidae) - Ozretić, Judita; Kević, Nives; Restović, Ivana; Bočina, Ivana, biologinja (2021)
The histological structure and histochemical characteristics of the digestive tract of five specimens of salema porgy (Sarpa salpa, L.) were analysed using haematoxylin-eosin, Alcian blue/PAS and orcein-Giemsa staining techniques. The digestive system of salema porgy consists of esophagus, stomach and intestines with associated organs such as liver, pancreas and gallbladder. The wall of esophagus, stomach, intestines and gallbladder has four distinctive layers: the mucosa, the submucosa, the muscular and outer layer, serosa or adventitia. The mucosa consists of two different layers: epithelium and lamina propria. Mucosa of the upper part of the digestive system is layered by single squamous epithelium, while those of lower part of the digestive system is layered by single columnar epithelium. The submucosa is a layer made of connective tissue and blood vessels. In most parts of the digestive system the muscular layer consists of two parts: circular and longitudinal. The exception is the muscular layer of the stomach fundus which has three layers: inner, medium and outer. The outermost layer in the esophagus is adventitia made of connective tissue, blood vessels and nerves. In the stomach, intestines and the gallbladder this layer is replaced by serosa. Histochemical analysis has shown that mucosal cells in all parts of the digestive tube contain acid mucopolysaccharides (MPS). The liver consists of hepatocytes separated by sinusoidal capillaries. The pancreatic tissue is scattered along the liver parenchyma and along the wall of pyloric caeca.The present study is the first record on digestive system histology of salema porgy showing that it is congruent to its feeding habits.
Histološka struktura i histokemijske karakteristike probavnog sustava salpe (Sarpa salpa , L.) istraživane su korištenjem hematoksilin-eozin, alcian plavo / PAS i orcein-Giemsa tehnikama bojenja. Probavni sustav salpe sastoji se od jednjaka, želudca i crijeva s povezanim organima poput jetre, gušterače i žučnog mjehura. Zid jednjaka, želudca, crijeva i žučnog mjehura ima četiri karakteristična sloja: sluznicu, submukozu, mišićni i vanjski sloj. Sluznica se sastoji od dva različita sloja: epitela i lamine proprije. Submukoza je sloj vezivnog tkiva s krvnim žilama. U većini dijelova probavnog sustava mišićni sloj sastoji se od dva sloja mišićnih vlakana: kružnih i uzdužnih. Izuzetak je mišićni sloj fundusa želudca koji ima tri sloja mišićnih vlakana: unutarnji, srednji i vanjski. Vanjski sloj jednjaka zove se adventitia i izrađen je od vezivnog tkiva, s krvnim žilama i živcima. U želudcu, crijevima i žučnom mjehuru ovaj sloj zamjenjuje seroza. Histokemijska analiza pokazala je da stanice sluznice u svim dijelovima probavne cijevi sadrže kisele mukopolisaharide (MPS). Jetra se sastoji od hepatocita razdvojenih sinusoidnim kapilarama. Tkivo gušterače raspršeno je duž jetrenog parenhima i duž zida piloričkih nastavaka. Ovo istraživanje je prvi zapis o histologiji probavnog sustava salpe koji pokazuje da je ona u skladu s prehrambenim navikama ispitivane ribe.
Bibliografija: str. 156-158.
Summary ; Sažetak.
Keywords: Ribe -- Salpa -- Sarpa salpa L. -- Probavni sustav -- Histološka struktura -- Histokemijske osobine